AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL KULIT BUAH KASTURI (Mangifera casturi Kosterm.) - Rahmi Muthia; Helmina Wati (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2018)
Mangifera casturi Kosterm is a typical plant of South Borneo that contains terpenoids, steroids, and phenolics compound. The aim of this research was to determine the antioxidant activity of M.casturi rind. The M.casturi rind was extracted continuously used soxhletion method with ethanol. Qualitative test of antioxidant activity in thin layer chomatography (TLC) with the mobile phase n-hexane : ethyl acetate (4 : 6). Quantitative assay using free radical scavenging (DPPH). The results obtained from the qualitative test showed ethanol extract from M.casturi rind had antioxidant activity. Quantitative assay showed ethanol extract from M.casturi rind and quercetin with a concentration 50 μg/mL was 97.87% and 97.98% respectively. The IC50 value from M.casturi rind and quercetin was 9.82 μg/mL and 4.17 μg/mL respectively. M.casturi rind have potent antioxidant activity.